Improving Children's Creativity Using Natural Materials from Leaves - Yofia Nur Afifah; Khoirun Nisa; Nurul Ismaiyah (Universitas Negeri Semarang, 2024)
The purpose of this study is to describe the design of printing activities using natural materials to increase children's creativity. The qualitative descriptive analysis method was chosen for data collection through observation, interviews, and documentation. Data reduction techniques, data presentation, and data analysis to draw conclusions show that leaf natural materials have the potential to support activities that increase creativity. The strategy to increase creativity in children is to carry out a printing activity based on natural materials by printing with natural leaf materials. It can be concluded that children's creativity can be increased through the activity of printing designs described based on natural materials obtained from the surrounding environment, the ability to explore is more maximal when early childhood is given instructions to get out of the comfort zone. The increase in early childhood creativity is obtained from fun activities, motor stimulation, sensory stimulation to stimulation of students' cognitive intelligence. Students complete the printing challenge with set rules to the freedom to channel their imagination